Patterns of Communicative Interaction of a Mathematics professor. Case study - Leguizamón Romero, José Francisco (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This study was developed in order to analyze patterns of communicative interactions in some mathematics lessons of the bachelor’s degree in Mathematics at Pedagogical and Technological University of Colombia (UPTC). The research is qualitative, interpretative and hermeneutic. A professor was taken as a sample and each session of his mathematics lesson was distributed in didactic configurations and the interactions of each configuration were analyzed. It should be pointed out that the most frequent interactions in the mathematics lesson are: the short question by the professor as well as the short answer by the student, the clarifications and short explanations given by the professor, the broad explanation by the professor and his own response. Therefore it was concluded that the lesson given by the professor is traditional-technological.